EVALUATING GENRE-BASED APPROACH ON SPEAKING PERFORMANCE ACROSS DIFFERENT ANXIETY LEVELS AMONG INDONESIAN EFL STUDENTS - Putra, Hendra; Hartono, Rudi; Mujianto, Januarius; Yulianti (English Review: Journal of English Education, 2025)
One of speaking performance is presentation the topic material. In presentation the topic material nursing students implement the genre-based approach. This study examines the effectiveness of genre-based approach to enhance speaking performance. This study employed One-Group Pretest-Post-test Design. To collect the data used questionnaire and pre-test and post- speaking test. In analyzing the data of questionaire used Horwitz et.al and grouped them into three level anxety. The result found that the effectiveness of genre-based approach to enhance speaking performance on EFL students for high level anxiety is significant. It can be seen from the p-value = 0.022 is smaller than α = 0.05. If the p-value < α, then the null hypothesis (H0) is rejected, and the alternative hypothesis (H1) is accepted.The effectiveness of genre-based approach to enhance speaking performance on EFL students for moderate level anxiety is not signficant because the p-value = 0.165 is greater than α = 0.05. If the p-value > α, then the null hypothesis (H0) is not rejected, and the alternative hypothesis (H1) is not accepted. The effectiveness of genre-based approach to enhance speaking performance on EFL students for low level anxiety is significant because the p-value = 0.001 is smaller than α = 0.05. If the p-value is very small like this, then the null hypothesis (H0) is rejected very strongly, and the alternative hypothesis (H1) is accepted very strongly. It can be concluded that the genre-based approach was found to significantly improve speaking performance in students with high and low anxiety, but not moderate anxiety.